Knowledge of the Effect of Pesticide Use in Vegetables and Fruits on Health and Environment among Consumers: A Descriptive Cross-sectional Study - Jyoti, Sabita; Yadav, Mukesh; Yadav, Anika; Sharma, Sakar (Nepal Medical College Journal, 2025)
According to the WHO, pesticides are chemical compounds that are used to kill pests, including insects, rodents, fungi, and unwanted plants (weeds) or it is any substance, or mixture of substances of chemical or biological ingredients intended for repelling, destroying, or controlling any pest, or regulating plant growth. Persistent organic pollutants circulate globally as a set of toxic chemicals that are persistent in the environment and can last for several years before breaking down. This study aims to find out the knowledge of consumers on effects of pesticide used in vegetables and fruits on health and environment. A descriptive cross-sectional study was conducted among visitors of patients, students, and staff at tertiary center after getting ethical approval from Institutional Review Committee. Individuals who know effects of pesticides on health were included in the study and those who did not give consent for study were excluded. Convenience sampling method was used. Out of 324 participants, 146 (45.10%) of participants reside in urban areas, followed by semi-urban 107 (33.0%) and rural 71 (21.90%). Organophosphates are the most common pesticides used on fruits and vegetables, 167 (51.54%). The risk of pesticide residues to health was known by 295 (91.0%) of respondents. According to the majority, 291 (89.80%) pesticides used are bad for the environment, and only 33 (10.20%) think that pesticide use is not bad for the environment. This descriptive cross-sectional study concludes diverse levels of knowledge among consumers regarding the effect of pesticide use in vegetables and fruits, as well as knowledge level influenced by education, income, and geographic location. There is an urgent need for accessible, clear communication through labelling and public education to bridge these gaps and to promote sustainable consumer practice.